Regulation of local bone remodeling mediated by hybrid multilayer coating embedded with hyaluronan-alendronate/BMP-2 nanoparticles on Ti6Al7Nb implants. Issue 44 (25th October 2016) - Shen, Xinkun; Zhang, Yarong; Hu, Yan; Luo, Zhong; Ma, Pingping; Li, Liqi; Mu, Caiyun; Huang, Ling; Pei, Yuxia; Cai, Kaiyong
Abstract : Hyaluronate-alendronate/BMP-2 nanoparticles were inserted into Gel/Chi multilayers on Ti6Al7Nb for enhancing BMP-2 stability and promoting local osteogenesis under osteoporosis. Abstract : Osteoporosis, a common bone disease, has been identified as a major obstacle for successful implantation. Therefore, the promotion of early mechanical fixation between implants and the surrounding bone can strongly increase the success rate of orthopedic operation in osteoporosis patients. In this study, functional hyaluronan-alendronate/BMP-2 (HA-Aln/BMP-2) nanoparticles were embedded into the Gel/Chi multilayers on Ti6Al7Nb surfaces (namely Ti6Al7Nb/LBL/NP) to endow the Ti6Al7Nb-based implant with local anti-osteoporosis properties. The release test showed that the loaded BMP-2 only slowly released along with the degradation of multilayers, and no burst release emerged at the early stage. In vitro cell experiments, including cell morphology, viability, alkaline phosphatase (ALP) activity, mineralization capacity and tartrate-resistant acid phosphatase (TRAP), demonstrated that the prepared Ti6Al7Nb/LBL/NP implants not only improved the proliferation and differentiation of osteoblasts but also inhibited the maturity of osteoclasts. Moreover, the in vivo tests of the push-out test, micro-CT and histological stains further verified that the Ti6Al7Nb/LBL/NP implant was more beneficial to promoting the local osseointegration between the natural bone and the implant when compared to those of the control groups after implantation for 3 months in osteoporotic rabbits. The study demonstrated a flexible method for effectively enhancing the early osseointegration between the implant and the native osteoporotic bone.